Efek Suplementasi Serat Chitosan dengan Omega-3 dalam Minyak Ikan Terhadap Trigliserida Plasma dan Kolesterol Total pada Pekerja Obes - Syarief, Fatimah (Jurnal Kedokteran Indonesia, 2011)
Background: The primary problem of dislipidemia include increases in total cholesterol, LDL cholesterol,triglyceride or decrease of HDL cholesterol. Omega-3 in fish oil supplementation has benefit on themanagement of hypertriglyceridemia and cholesterol This study aimed to determine the effect ofchitosan fiber supplementation with omega-3 in fish oil on plasma triglyceride and total cholesterol inobese employeesMethods: Thirty-eight obese employees were assigned into 2 groups, equalized on the basis of theirbody mass index (BMI > 25 kg/m2). Twenty two obese employees received supplements providing 3 gomega-3 and 16 obese employees received 3 g omega-3 and 3 gr chitosan daily for 21 days. Plasmatrigliceryde and total cholesterol were measured on days 0 and 22. Confounding factors of this studywere fiber intake during study and total cholesterol before supplementation. Linear regression analysiswas run on SPSS 17 to determine the difference in triglyceride and total cholesterol levels betweenthe two groups while controlling for the confounding factors.Results: The study showed that total cholesterol on chitosan and omega 3 group was lower thanomega-3 group. The difference of total cholesterol between groups was statistically significant.However, there was no difference in triglyceride between groups.Conclusion: Chitosan supplementation along with omega-3 supplementation has a beneficial effect inlowering total cholesterol in 20-54 years old obese employeesKeywords: obese, omega-3, chitosan, triglyceride, total cholesterol